Innovation for European competitiveness and cohesion: Opportunities and difficulties of co-evolution - Lena Tsipouri (Science and Public Policy, 2004)
The European Union aims to become the most competitive and dynamic knowledge-based economy in the world by 2010. Nevertheless, half the Europe-25 Member States possess limited innovation capacities. This article argues that the co-evolution patterns of physical and social technologies indicate two possible scenarios: either the forward-looking elements will start a chain reaction mobilising the rest of the national system, as in Ireland; or the dynamic elements will integrate sectorally and transnationally to the global system, leaving the rest of the economy in a permanent low-cost and low-competitiveness trap. The former is a win-win scenario for the European system of innovation, whereas the latter is second-best.